1408 - Mikael Hyrist; Cusack, John.; Samuel L Jackson; Mary McCormack; Tony Shalhoub; Len Cariou (Weinstein Company USA, 2007)
Based on a short story by Stephen King, a man who specializes in debunking the paranormal checks into the infamous room 1408 in the Dolphin Hotel, only to the terror is real.
Language(s): English Subtitle(s): Turkish
Keywords: Horror